Rising to the Zero Hunger Challenge - Sundaram, Kwame, Jomo (2014)
Event organized by IFPRI, FAO, and Community for Zero Hunger "The Zero Hunger Challenge - Achieving the Right to Food for All" presentation by Jomo Kwame Sundaram, FAO on January 30, 2014 https://www.ifpri.org/event/zero-hunger-challenge